2005
DOI: 10.1128/iai.73.4.2083-2093.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus equi-Specific Cytotoxic T Lymphocytes in Immune Horses and Development in Asymptomatic Foals

Abstract: Rhodococcus equi is an important cause of pneumonia in young horses; however, adult horses are immune due to their ability to mount protective recall responses. In this study, the hypothesis that R. equi-specific cytotoxic T lymphocytes (CTL) are present in the lung of immune horses was tested. Bronchoalveolar lavage (BAL)-derived pulmonary T lymphocytes stimulated with R. equi lysed infected alveolar macrophages and peripheral blood adherent cells (PBAC). As with CTL obtained from the blood, killing of R. equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(40 reference statements)
1
29
0
2
Order By: Relevance
“…It is important to consider that a protective immune response is the result of combination and interaction among the many arms of the immune system (innate and acquired mechanisms). Indeed, foal mMOs revealed a measurable response to R. equi infection and other studies have shown their competence at interacting with cytotoxic lymphocytes (44,64).…”
Section: Discussionmentioning
confidence: 78%
“…It is important to consider that a protective immune response is the result of combination and interaction among the many arms of the immune system (innate and acquired mechanisms). Indeed, foal mMOs revealed a measurable response to R. equi infection and other studies have shown their competence at interacting with cytotoxic lymphocytes (44,64).…”
Section: Discussionmentioning
confidence: 78%
“…A subsequent study confirmed the presence of R. equispecific, MHC class I-unrestricted CTLs in foals (Patton et al, 2005). However, CTLs were not present during the first few weeks of life -the period at which foals are considered most susceptible and probably first infected.…”
Section: Discussionmentioning
confidence: 78%
“…The following formula for percentage specific lysis was used: [(E2S)/(T2S)]6100, where E is the mean of three test wells, S is the mean spontaneous release from three target cell wells without effector cells, and T is the mean total release from three target cell wells with 2 % Triton X-100 (Sigma-Aldrich). As reported previously, significant lysis was defined as 3 SEM above the negative-control value (McGuire et al, 1994;Patton et al, 2004Patton et al, , 2005Siliciano et al, 1985).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cytotoxic T lymphocytes are involved in the control of several important intracellular pathogens of horses, including equine herpes virus-1 (1-7), equine arteritis virus (8), and Rhodococcus equi (9,10). In horses infected with equine infectious anemia virus (EIAV), a lentivirus with a world-wide distribution, CTL are critical in the control of viral replication and clinical disease (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%